Chapter Nursing Students' Future Employment Preferences and the Real Demands of Patients using the Health Services. A Qualitative Study on a Group of Final-Year Students at the University of Padua - Bobbo, Natascia (Studies on Adult Learning and Education, 2018)
Increasing life expectancy and the growing number of chronic diseases have changed the kind of patients who need to be assisted. This paper presents a qualitative study conducted with a group of nursing students near graduation, aimed at describing and discussing vocational preferences and desirable healthcare settings for future employment